Language learning with a social networking site on a mobile device: identifying inhibiting issues - Gabarre, Serge; Gabarre, Cecile; Din, Rosseni; Shah, Parilah; Abdul Karim, Aidah (2012)
For students enrolled in Malaysian institutions of higher learning, mobile phones and social networking sites are ubiquitous. However, these are mostly used for activities which are not related to learning. Both mobile devices and social networking sites offer opportunities to educational technologists.This paper reports on a qualitative research project which was conducted to concurrently integrate the two technologies in a French as a foreign language course. A meta-analysis of the literature was conducted to both evaluate the current extent of the knowledge in the field, and to identify potential applications for these technologies. The researchers ensured that the students selected for this research were provided, when necessary, with mobile phones and access to mobile internet. Course material were distributed on Facebook and accessed with the students’ mobile phones. Learner-created content in the target language was uploaded to the social networking site and shared by the students. Qualitative data was collected through group and one-on-one interviews, before being analyzed in a systematic grounded research fashion. Findings from these revealed inhibiting issues which may be attributed to both mobile phones and the social networking site. These issues are contextualized in light of other research which experienced similar concerns. The authors propose solutions to alleviate those issues and advocate for the use of both technologies in the foreign language course.